PENGUATAN KEMAMPUAN BERPIKIR MATEMATIS UNTUK OLIMPIADE MATEMATIKA - Umbara, Hanifa Dina Aulia Dewi; Ningrum, Yunia Jumita; Rachmi, Cut Nadia; Bulubaan, Santy; Syaputra, Muhammad Rizky; Putri, Nadyati; Rahmatin, Tsania; Jupri, Al; Kusnandi, Kusnandi (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service aims to improve the mathematical thinking competence of teachers and students in facing mathematical Olympiads through two main activities: training for teachers and mathematical Olympiad coaching for students. Strengthening mathematical thinking competency is very important in preparing teachers and students to face the challenges of mathematics olympiads that demand high-level understanding, analysis, and problem solving. This activity was carried out by students of the Master's Program in Mathematics Education at Universitas Pendidikan Indonesia, with a focus on strengthening mathematical thinking strategies and developing skills to tackle mathematical Olympiad problems. The training for teachers was conducted online for 4.5 hours and attended by 530 participants from across Indonesia, while the student coaching took place at SMAN 1 Katapang for 5 hours with 19 participants. Quantitative evaluation through closed-ended questionnaires showed that the activity succeeded in suporting teachers’ mathematical thinking competencies and supporting students in solving olympiad-level problems. The collaboration between academics and educational practitioners in this activity is expected to make a significant contribution to improving the quality of mathematics education in Indonesia and strengthening students' competitiveness in mathematical Olympiads even on an international scale